(NiSTORIQ RUSSKOGO LITERATURNOGO QZYKA (B:s (NhRESTOMATIQ (B: (Nu^EBNOE POSOBIE (B/s - (NkOVIN(B, (Na(B.(Nn(B.s ((NmOSKWA (B:s (NwYS[AQ [KOLA (B,s, 1989)
(NbIBLIOGR(B. (NW PRIME^(B.: (NS(B. 313-315s
(NzAGL(B. 1-(NGO IZD(B.: (NhRESTOMATIQ PO ISTORII RUSSKOGO LITERATURNOGO QZYKAs
Keywords: (NrUSSKIJ QZYKs